EVALUATION OF FARMERS' PRACTICES AND KNOWLEDGE ON THE SAFE USE OF PESTICIDES IN ALGERIA: CASE OF THE REGION OF EL-OUED - Saighi Imane; Dadamoussa Med Lakhdar; Belaroussi Med El Hafed; Boumada Abdelbasset; Iddir-Ighili Hakima (Journal of Animal and Plant Sciences, 2025)
Modern agriculture's heavy reliance on pesticides presents serious health risks and adds to environmental deterioration. This study looked at farmers' sources of information about relevant risks and assessed their knowledge and actions regarding the safe use of pesticides. In the south-eastern Algerian district of El-Oued, which ranks third in the country for potato cultivation and is renowned for its extensive vegetable output, 136 farmers participated in a field survey. According to the report, 131 commercial pesticide products were used. 41% of respondents said they utilized generic substitutes, whilst 59% said they used branded international products. The primary objectives included weeds, fungal diseases, and insect pests like tomato leaf miner, aphids, and whiteflies. The most commonly utilized active ingredients were metribuzin, fosetyl-aluminum, and abamectin. The majority of farmers did not follow basic safety precautions, despite 71% of them acknowledging the dangers of pesticide exposure. The risk of environmental contamination increased since pesticide containers were frequently disposed of improperly and personal protective equipment was rarely used. Additionally, more than 60% of the farmers solicited guidance from unofficial sources like neighbors or nearby pesticide vendors. The results show a substantial discrepancy between safe practices and knowledge. In order to guarantee the safe and sustainable use of pesticides, these findings highlight the critical need for enhanced farmer training, efficient regulatory enforcement, and the creation of focused awareness campaigns.
Keywords: Agricultural extension; awareness; chemical exposure; farmer behavior; personal protective equipment; pest control; rural knowledge; safety compliance